The effect of weighted blankets on sleep and related disorders: a brief review - Yu, Jie; Yang, Zhenqing; Sun, Sudan; Sun, Kaili; Chen, Weiran; Zhang, Liming; Xu, Jiahui; Xu, Qinglin; Liu, Zuyun; Ke, Juan; Zhang, Lisan; Zhu, Yubo (Frontiers in Psychiatry, 2024)
Background: Sleep disorders such as insomnia can lead to a range of health problems. The high risk of side effects and drug abuse of traditional pharmacotherapy calls for a safer non-pharmacotherapy.To examine the use and efficacy of weighted blankets in improving sleep and related disorders in different populations and explore the possible mechanisms.Methods: A literature search was conducted using PubMed, Embase, Web of Science, MEDLINE, Cochrane Library and CNKI databases. Eligible studies included an intervention with weighted blankets and outcomes covering sleep and/or related disorders (behavioral disturbance, negative emotions and daytime symptoms). Studies using other deep pressure, compression, or exerciserelated interventions were excluded.Conclusions: Most of the included studies showed that weighted blankets could effectively improve sleep quality and alleviate negative emotions and daytime symptoms in patients with sleep disorders, attention deficit hyperactivity disorder, autism spectrum disorder, and other related disorders, with a possible mechanism of deep pressure touch.Recommendations: Weighted blankets might be a promising tool for sleep interventions among individuals with sleep disorders in clinical settings. More high-quality and large-scale randomized controlled trials are needed to further validate the safety and efficacy of weighted blankets and explore precise mechanisms.